Em nome dos professores? : inserção profissional e carreiras políticas - Figueiredo, Taís Cristina Samora de (2012)
This dissertation studies the methods of political career of teachers in the State of Sergipe (Brazil). The main objective was to analyze the routes of politicians elected by Sergipe, who self-identified as teachers in the parliamentary elections of 2010, and in elections to the City Council of the Capital of the State, Aracaju, in the year 2008. The studied group is composed of seven politicians (1 Congressman, 4 deputies and 2 aldermen). Among the methodologies, was prioritized to direct observation, with uses of interviews with politicians and aides and election data collection. Also was gave emphasis on forms of action and the political representation of Deputies and councilmen. In the first chapter, I discuss the teachers professionalization and its relationship with politics, also present data on teachers occupation in the prefectures and the municipalities of Sergipe. In the second chapter, I discuss how the profession is used for entry into politics, ressaltan the forms of action in teaching and politics. In the third chapter, dealing with parliamentary activities, observing how they say represents various interests.